Epigallocatechin gallate-β-lactoglobulin nanoparticles improve the antitumor activity of EGCG for inducing cancer cell apoptosis. (December 2017) - Wu, Min; Jin, Jianchang; Jin, Peng; Xu, Yongquan; Yin, Junfeng; Qin, Dingkui; Wang, Kai; Du, Qizhen
Graphical abstract: Highlights: β-Lactoglobulin (β-LG) with EGCG to form stable co-assembled nanoparticles (Eβ-NPs). Eβ-NPs inhibited tumour cell proliferation greater activity than native EGCG. Cancer cells treated with Eβ-NPs showed increased apoptosis. Eβ-NPs-induced apoptosis is more effective than EGCG in Akt-mediated phosphorylation. Eβ-NPs alters pro/anti-apoptotic proteins including Bcl-2 family members and caspases. Abstract: (−)-Epigallocatechin-3-gallate (EGCG), the major catechin in green tea, is a potent antioxidant with numerous reported health benefits, such as anti-proliferative and pro-apoptotic effects. We combined thermally modified β-lactoglobulin (β-LG) with EGCG to form stable co-assembled nanoparticles (Eβ-NPs). The Eβ-NPs inhibited the proliferation of human malignant melanoma cells A375 and human eosophageal carcinoma cells TE-1 with 69.0% and 63.7% greater activity than EGCG, respectively. Cancer cells treated with Eβ-NPs showed increased apoptosis, suppressed proliferation and appreciable cell cycle inhibition. A plausible mechanism of Eβ-NPs-induced apoptosis was proposed, in which Eβ-NPs were more effective than native EGCG for Akt-mediated phosphorylation, which altered several pro/anti-apoptotic proteins including Bcl-2 family members and caspases. Thus, Eβ-NPs have the potential to improve the chemopreventive effect of EGCG in functional foods.